AKAR PENYEBAB DEFORESTASI DI SEKITAR SUNGAI PEMERIHAN PERBATASAN TAMAN NASIONAL BUKIT BARISAN SELATAN, LAMPUNGBARAT - Suyadi, Suyadi; Gaveau, David Luc Andre (BERITA BIOLOGI, 2007)
The destruction of lowland tropical forests represents one of the greatest threats to biodiversity in Sumatras third-largest protected area, the Bukit Barisan Selatan National Park (BBSNP). Here, we integrate time-series satellite and socio-economic information in a Geographic Information System (GIS) to unravel the root causes of deforestation in two encroachments(Cawangaro and Sumbersari) near Pemerihan River bordering BBSNP.Cawangaro was originally developed as an enclave in 1965.Sumbersari remained forested until 1978.Both encroachments experienced higher deforestation rates during the late 1970s and in 2005. Our GIS combined with historical records show that large-scale logging, high coffee price and village development plans (perluasan lahan usahatani penduduk) drove deforestation during late 1970s. Throughout the 1980s and until 1997/1998, deforestation rates have been negligible as strong law enforcement measures were adopted by the Government to protect biodiversity during the implementation of Indonesias first land-use plan (TGHK). Since the 1997-1998 Asian economic crisis, deforestation rates have increased again. Results from socio-economic surveys showed that illegal logging has become one major factor driving agricultural encroachments in Pemerihan since 1998. Local tycoons have exploited the parks timber since Suhartos fall, probably due to the decline of law and order. While timber extraction itself has caused very limited damage to the forest, this illegal activity sparked a land race among farmers inside the park.